Effects of occasional tillage on soil physical and chemical properties and weed infestation in a 10-year no-till system - Diop, Massamba; Beniaich, Adnane; Cicek, Harun; Ouabbou, Hassan; El Gharras, Oussama; Tanji, Abbès; Bamouh, Ahmed; Dahan, Rachid; Zine El Abidine, Aziz; El Gharous, Mohamed; El Mejahed, Khalil (Frontiers in Environmental Science, 2024)
An on-farm trial was implemented in 2020 to test the effects of occasional tillage (OT) in Morocco with a long-term no-tillage (NT) system and rainfed field crops: durum wheat (Triticum durum), faba bean (Vicia faba minor), and chickpea (Cicer arietinum). Four treatments were established: continuous NT with crop residues maintained ("NT+residue"); continuous NT with crop residues not maintained ("NT-residue"); shallow inversion tillage ("shallow OT"); deep non-inversion tillage ("deep OT"). We assessed the effect of these treatments on soil physical and chemical properties in 0-10 and 10-20 cm soil depths after crop harvest of the 2020-2021 (year 1) and 2021-2022 (year 2) growing seasons corresponding to one and two years after OT, respectively. In addition, we evaluated the effect of the treatments on weed populations and the effect of the legume crop rotated with wheat on soil nitrogen (N) and weed density. In year 1, deep OT reduced water content at field capacity and available water capacity at 0-10 cm compared to continuous NT; cation-exchange capacity (CEC) under deep OT was lower than in NT-residue and NT+residue at 0-10 cm and 10-20 cm, respectively. Furthermore, deep OT increased ammonium-N (NH4-N) at 0-10 and 10-20 cm compared to NT+residue but reduced exchangeable potassium (K) at 10-20 cm depth compared to NT-residue. In year 2, shallow OT had lower total porosity at 10-20 cm compared to NT+residue, while shallow and deep OT recorded higher water-stable aggregates at 0-10 cm compared to NT+residue; at 10-20 cm, deep OT recorded lower CEC compared to NT+residue. However, deep OT had higher nitrate-N (NO3-N) and available sulfur (S) compared to NT-residue. In year 1, 50 days after OT, deep OT reduced weed density by 46% compared to NT+residue, while in year 2, 406 days after OT, shallow OT reduced weed density by 53% compared to NT-residue. Occasional tillage didn't help to reduce the stratification of soil nutrients in NT. Regarding the effect of the legume rotated with wheat, faba bean appeared to be the better preceding or following crop of wheat for higher residual soil mineral N and lower weed infestation, as compared to chickpea.